Human rights : an interdisciplinary approach - Freeman, Michael, 1936- (Cambridge, UK : Polity Press ; Malden, MA : Blackwell, 2002)
"The book will appeal to students in the social sciences, as well as students of human rights law who want an introduction to the non-legal aspects of their subject. It will also be read by scholars interested in ethics and the social sciences, as well as the general reader"--
Introduction: thinking about human rights -- Origins: the rise and fall of natural rights -- After 1945: the new age of rights -- Theories of human rights -- The role of the social sciences -- Universality, diversity and difference: culture and human rights -- Idealism, realism and repression: the politics of human rights -- Development and globalization: economics and human rights -- Conclusion: human rights in the twenty-first century.
Includes bibliographical references (pages 179-194) and index.
Keywords: Human rights; Human Rights